Characteristics of the Yuan dynasty: Reflections on several issues from Mongol Yuan history. Issue 1 (2nd January 2018) - Fan, Zhang
Abstract: This article discusses the special position the Yuan dynasty (1260-1368) occupied in Chinese history. Of all the dynasties, the Yuan established by the Mongols showed its peculiarity. To borrow Karl Wittfogel's term, the Yuan was a typical "conquest dynasty." The historical significance of the Yuan and its predecessor—the Mongol empire (1206-1259) lay in two areas. One was that it ended the conflicts of various ethnic groups on the Mongolian steppe. The other was that it revived the idea of "patrimonialism" in the course of Chinese history. But Yuan's rule did not last long, which was attributed to its slow "Sinicization." Nonetheless, the Yuan exerted a great impact on the development of Chinese history, deserving more studies of the extent and depth of the impact.